The dichotomy between Society and Nature in the Ebro reservoir: Preserving a traditional way of life or prioritising national benefit - Conde-Oria, Francisco (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
The origins of this problem go back to one of the many conflicts between society and nature that the hydrological policies of the late 19th and early 20th centuries in Spain caused. The construction of the Ebro reservoir, defended as the most economical work of the time in relation to the volume of the reservoir, was presented as a solution to the frequent droughts in the Ebro valley. The construction of irrigation and power plants promised to boost the country’s economy and would mean significant demographic, industrial and commercial growth throughout the area. Upstream, however, a region inhabited by more than 15,000 people would see everything they had worked for and grown up with disappear under the water. These people, who were mainly livestock farmers, had terraced land with fertile soil, crops, fruit trees, mining and some glass and crystal factories, all of which are in danger of disappearing as a result of the construction of the reservoir. Lorenzo Pardo, the project’s architect, wanted the active participation of the people affected. Although the project had its supporters, it was overwhelmingly opposed by those who saw it as a serious threat to their way of life. The proposed compensation was insufficient to make up for the huge losses in livestock, agriculture, mining, glassmaking and infrastructure, especially roads. The outcome of the conflict, after many twists and turns, ended with the water covering everything in its path after a civil war that left the country in a complicated situation. Many of those neighbours are no longer alive to recount their experiences, but the story lives on in the minds of the few neighbours who still resist in the surrounding area, and in the remnants that appear each time the level of the reservoir drops